Pengaruh Budaya Organisasi dan Kepemimpinan terhadap Kinerja BRI Kantor Cabang Pattimura Semarang - Tania, Eritha; Hadi, Sudharto Prawata (Jurnal Ilmu Administrasi Bisnis, 2020)
Performance is a picture of the level of achievement of the implementation of an activity or program or policy in realizing the goal, aim, mission, and vision of the organization as stated in the strategic plan. In this case, company expects high performance. But based on data obtained from BRI Pattimura Semarang Branch Office shows fluctuation in the financial and customer achievements on savings and loan transaction from 2017 to mid 2019. It is suspected that the fluctuation is caused by factors of organization culture and leadership, so this research aims to determine wether corporate culture and leadership have an influence on performance of BRI Pattimura Semarang Branch Office. The type of this research is explanatory research, there is 50 respondents was taken as samples from 99 employees. Sampling techniques using simple random sampling and data collection techniques using questionnaire, interview, and literature study. The analytical tool used is SPSS 21.0 with a validity test, reliability test, correlation coefficient test, correlation determination, simple and multiple regression analysis, t test and F test. Based on the results of the analysis it can be concluded that the corporate culture and leadership influence the performance of BRI Pattimura Semarang Branch Office as evidenced through multiple regression testing resulting in regression values of 0.176 and 0.376. BRI Pattimura Semarang Branch Office needs to ensure that all employees implement the organization culture (BRILian) to the maximum, being able to treat and coordinate employes well in order to achieve company goals and improve company performance.